Breakwater geometric model base on mangrove roots structure - Mohamad Jusoh, Mohamad Zamin (2015)
In year 2013, the Department of Irrigation and Drainage Malaysia indicates that 29% or 1,394 km out of 4,809 km of the country’s coastline are facing erosion. The coastal erosion had caused 1% of mangrove forest area to continue decline each year. Although mangroves were affected by the erosion but the erosion rate was reduces in the area which mangroves inhabited. Hence,researchers had conducted studies on wave dissipation process in mangrove forest structure that concentrated at west coast of the Malaysia peninsular. Contrarily, this study had taken different approach by investigating on a sole mangrove trees structures at east coast of Malaysia peninsular. The study were focused in the geometrical properties of the mangrove roots and the water flow structure within the mangrove roots area of the Avicennia marina (A.marina) and Rhizophora apiculata (R. apiculata) mangrove species. The roots properties were investigated by conducting a field work at Pantai Marina,Kemaman where the geometrical coordinate of each roots of A. marina and R.apiculata species were collected using grids. Henceforth, a 2D model of the mangrove roots was constructed using meshing software. The simulations were conducted in Computational Fluid Dynamic software using unsteady Spalart-Allmaras turbulence model, water liquid material and by setting the velocity inlet in boundary condition to 6 m/s. From the investigation, it was found that the mangrove roots tend to grow around the mangrove primary trunk which facing the direction of the water traveled. It had been observed that there was large density of mangrove roots within the distance 100 cm to 150 cm from the primary trunk. The simulation result shows that mangrove roots were capable to decrease the initial velocity 6 m/s of water flow to almost 2 m/s. The breakwater model also shows that the geometrical coordinate and the distance between structures were related to the velocity deficit rate. Each structure was arranged in zigzag pattern and the distance of the structure was placed within the maximum range of three times of the structures cross section diameter to create optimum velocity dissipation rate. Thus, the study had found that both mangrove roots and the breakwater models were capable reducing the velocity to 60 %. The velocity deficit also was related to the roots density, structure and coordination. Henceforth, the finding could contribute to the future construction of breakwater along the coastline in order to overcome the current coastal erosion problem or in the near future.